Complex small-molecule architectures regulate phenotypic plasticity in a nematode. - Bose, Neelanjan; Ogawa, Akira; Von Reuss, Stephan; Yim, Joshua J; Ragsdale, Erik J; Sommer, Ralf J; Schroeder, Frank C (My University, 2012)
Chemistry the worm's way: The nematode Pristionchus pacificus constructs elaborate small molecules from modified building blocks of primary metabolism, including an unusual xylopyranose-based nucleoside (see scheme). These compounds act as signaling molecules to control adult phenotypic plasticity and dauer development and provide examples of modular generation of structural diversity in metazoans.